دور الرقمنة في تحسين الآداء الوظيفي - جويرية نيد; كنزة بن قلية (جامعة الوادي - University of Eloued, 2025)
" تسعى هذه الدراسة على التعرف على دور الرقمنة في تحسين الآداء الوظيفي لدى موظفي كلية الحقوق و العلوم السياسية –جامعة الوادي، فالمؤسسات تبنت تكنولوجيا الإتصال الحديثة، المتمحورة في الرقمنة، لاسيما المؤسسات الجامعية و ذلك بتطبيق الأسس الخاصة بعملية الرقمنة في مختلف إداراتها، و يبرز دور الرقمنة في الجامعات من خلال تحسين آدائها الوظيفي و تسهيل سير العمل للأساتذة و الموظفين و حتى الطلبة، انطلقت هذه الدراسة من التساؤل الرئيسي التالي:  كيف تساهم الرقمنة في تحسين الأداء الوظيفي لدى موظفي جامعة الوادي ؟ ينبثق تحته سؤالين فرعيين:  هل وجود تكنولوجيا المعلومات له دور في تحسين الآداء الوظيفي ؟  هل الإتصال الرقمي له دور في تحسين الآداء الوظيفي ؟ * تندرج هذه الدراسة ضمن البحوث الوصفية من خلال استخدام المنهج الوصفي لأنه الأنسب في هذه الدراسة لمعرفة واقع الدراسة و جوانبها و وصفها و تحليلها، بمجتمع قدره 30 مفردة لذلك تم استخدام العينة القصدية لمجتمع الدراسة، باستبيان موزع على مجموع الموظفين بكلية الحقوق و العلوم السياسية. و بعد التحليل و التفسير توصلنا إلى النتيجة التالية:  الرقمنة ليس لها دور في تحسين الآداء الوظيفي. أيضا تم التأكد من صحة الفرضيات الفرعية كما يلي:  تكنولوجيا المعلومات ليس لها دور في تحسين الآداء الوظيفي.  الإتصال الرقمي ليس له دور في تحسين الآداء الوظيفي. " This study seeks to identify the role of digitization in improving the job performance of employees at the Faculty of Law and Political Science - University of Eloued, Institutions have adopted modern communication technology, centered on digitization, especially university institutions, by applying the foundations of the digitization process in their various departments. The role of digitization in universities is highlighted by improving their job performance and facilitating the workflow for professors, employees and even students This study was based on the following main question:  How does digitization contribute to improving job performance among Eloued University employees? Two sub-questions arise from this:  Does the presence of information technology play a role in improving job performance?  Does digital communication have a role in improving job performance? *This study falls within the descriptive research by using the descriptive method because it is the most appropriate in this study to know the reality of the study and its aspects and describe and analyze it, with a community of 30 individuals, so the intentional sample was used for the study community, with a questionnaire distributed to all employees in the Faculty of Law and Political Science. After analysis and interpretation, we arrived at the following conclusion: - Digitization has no role in improving job performance. The following sub-hypotheses were also confirmed: - Information technology has no role in improving job performance. - Digital communication has no role in improving job performance.
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل
Keywords: الآداء الوظيفي; الرقمنة; Digitization; Job performance